Highly dispersed Pt studded on CoOx nanoclusters for CO preferential oxidation in H2. Issue 20 (13th May 2020) - Cai, Jiaming; Liu, Zhang; Cao, Kun; Lang, Yun; Chu, Shengqi; Shan, Bin; Chen, Rong
Abstract : Highly dispersed Pt studded on CoO x catalysts are designed and fabricated by selective atomic layer deposition method for enhanced CO preferential oxidation performance. Abstract : Carbon monoxide (CO) preferential oxidation (PROX) is regarded as a promising method for hydrogen purification. Herein, the design and synthesis of highly dispersed Pt studded on CoO x catalysts are reported. The catalysts exhibit nearly 100% CO conversion and selectivity towards the CO PROX reaction under H2 stream at room temperature. The superior catalytic performance can be attributed to the unique structure. The Pt is selectively studded on CoO x nanoclusters to maximize the highly active metal–oxide interfaces. The Pt loading is reduced to ∼0.8%, which is one of the lowest reported loadings for Pt-based CO PROX catalysts. The kinetics studies reveal that the composite Pt–Co catalysts have a weaker CO adsorption and lower O2 activation barrier, which can increase the CO oxidation rate and suppress the H2 oxidation rate. In addition, it is found that the CoO x promotor in a lower chemical oxidation state is critical for the improved activity. Theoretical simulations reveal that the energetic route of CO oxidation in H2 for Pt/CoO is more active than that for a Pt/Co3 O4 surface.